Estado del arte de correlaciones para el modelamiento del fenómeno de transferencia de masa en columnas de extracción líquido - líquido (2018)
MESH equations model does not contemplate the mass transfer phenomena across the interphase in fluid-fluid separation operations even when they are present, nevertheless, there must be included when a rigorous simulation is going to be carried out in order to propose a real separation operation design. Several theories have been proposed (with deviations about 20%) for the mass transfer coefficient estimation resulting in both theoretical and empirical equations in the last fifty years. It is presented a state of the art about the available correlations for the mass transfer modeling in liquid-liquid extraction columns, that is: models for the infinite dilution diffusion coefficient, concentrated-solution diffusion coefficient, mass transfer coefficient and some properties calculation, which is considered useful for the MERSHQ model in liquid.liquid extraction columns.